Shifting power to the periphery: the impact of decentralisation on forests and forest people - Resosudarmo, I.A.P. (Institute of Southeast Asian Studies, 2003)
After decades of central government control, the recent decentralization laws devolved authority in many areas, including natural resource management, to local governments. This article examines the initial process of decentralization in Indonesia within the context of forestry. Preliminary analyses suggest that decentralization has profoundly affected the course of forest resource management, though in many cases it has also been influenced by the spirit of reformasi. Local governments, motivated both by necessity and opportunity, attempt to generate local revenues from forest resources without adequate consideration of the social and environmental consequences. It appears that with decentralization, local people may only gain limited short-term benefits from timber production.